x²-2amox+a²m²o²-t²e³=0 como resolve-la?
Soluções para a tarefa
Respondido por
19
x² - 2amox + a²m²o² - t²e² = 0
É uma equação de 2º grau:
a = 1
b = - 2amo
c = a²m²o² - t²e²
Fórmula de Bháscara:
x = { - b ± √[ b² - 4 . a . c ] } / ( 2 . a )
x = { - ( - 2amo) ± √[ (-2amo)² - 4 . (1) . (a²m²o² - t²e²) ] } / ( 2 . 1 )
x = { 2amo ± √[ 4a²m²o² - 4a²m²o² + 4t²e² ] } / 2
x = { 2amo ± √[ 4t²e² ] } / 2
x = { 2amo ± 2te } / 2
x' = { 2amo + 2te } / 2
x' = amo + te
x" = { 2amo - 2te } / 2
x" = amo - te
É uma equação de 2º grau:
a = 1
b = - 2amo
c = a²m²o² - t²e²
Fórmula de Bháscara:
x = { - b ± √[ b² - 4 . a . c ] } / ( 2 . a )
x = { - ( - 2amo) ± √[ (-2amo)² - 4 . (1) . (a²m²o² - t²e²) ] } / ( 2 . 1 )
x = { 2amo ± √[ 4a²m²o² - 4a²m²o² + 4t²e² ] } / 2
x = { 2amo ± √[ 4t²e² ] } / 2
x = { 2amo ± 2te } / 2
x' = { 2amo + 2te } / 2
x' = amo + te
x" = { 2amo - 2te } / 2
x" = amo - te
biamarques20:
obrigada ! <3
Perguntas interessantes
Português,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás